Using Hyperfocal Distance in Close-Range Photogrammetry for Indoor Modelling - E. Sommer; M. Koehl; P. Grussenmeyer (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Photogrammetry has recently gained in popularity for surveying buildings and exterior structures, thanks in particular to the use of drones, terrestrial or aerial imagery, and other devices that allow quality images to be obtained with sufficient distance. These approaches are ideal for capturing exterior architectural details where space allows greater flexibility to take pictures. However, when it comes to indoor surveys, spatial constraints and limited distance make it difficult to acquire quality data. In confined spaces, control of depth of field becomes an essential parameter for obtaining sharp images, which are essential to generate accurate 3D models. In this context, the hyperfocal distance is used and demonstrated as an effective approach for optimizing terrestrial and indoor photogrammetry. Hyperfocal distance enables depth of field to be maximised without the need for frequent optical adjustments or changes in position during shooting. This technique is particularly advantageous in limited spaces where recoil is difficult to adjust, thus avoiding constant intervention on lens parameters and enabling it to be properly calibrated. Thanks to this approach, it is possible to obtain a homogeneous sharpness on each shot, for elements at different distances, enhancing the accuracy of the data and the quality of the 3D models generated. This method has been applied to the throne room at Trifels castle in Germany. By using the hyperfocal distance, complex details were captured on site, enabling optimized data processing afterward. The model obtained is compared with surveys carried out by laser scanners, both terrestrial and mobile, enabling to validate the accuracy and repeatability of this method in a heritage documentation and conservation context. Finally, the various potential applications for the obtained data are explored, depending on the final objectives, whether for analysis or for display and communication to the general public. This processing and optimisation stage is part of an approach to enhance the value of built heritage, making old architectural elements accessible and understandable, while ensuring faithful digital conservation.